2021
DOI: 10.3389/fpls.2021.760589
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcriptome and Proteome Analysis to Elucidate Salt Tolerance Strategies of the Halophyte Panicum antidotale Retz

Abstract: Panicum antidotale, a C4 monocot, has the potential to reclaim saline and drylands and to be utilized as fodder and forage. Its adaptability to survive saline stress has been proven with eco-physiological and biochemical studies. However, little is known about its molecular mechanisms of salt tolerance. In this study, an integrated transcriptome and proteome analysis approach, based on RNA sequencing and liquid chromatography tandem mass spectrometry (LC-MS/MS), was used to identify the said mechanisms. Plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 80 publications
3
8
0
Order By: Relevance
“…Similarly, the quinoa plant exhibited markedly increased proline, TSS, and GB contents under drought stress (Figure 4). However, in saline conditions, plants uptake inorganic ions, especially Na + , in large amounts to achieve osmotic adjustment (Hussain et al, 2023;Sun et al, 2020).…”
Section: Salinity Promotes Inorganic Ions Absorption In Quinoamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the quinoa plant exhibited markedly increased proline, TSS, and GB contents under drought stress (Figure 4). However, in saline conditions, plants uptake inorganic ions, especially Na + , in large amounts to achieve osmotic adjustment (Hussain et al, 2023;Sun et al, 2020).…”
Section: Salinity Promotes Inorganic Ions Absorption In Quinoamentioning
confidence: 99%
“…However, plants grown under combined stress showed higher antioxidant enzymes' activity than plants grown under single drought and salinity (Figure 5). Recently, some studies reported that accumulation of osmolytes, (ROS)-scavenging enzymes, antioxidant system and phytohormones (ABA) production was more pronounced in combined stress conditions (i.e., drought and salinity) than in individual stress in different plants including quinoa (Abbas et al, 2023;dos Santos et al, 2022;Hussain et al, 2020Hussain et al, , 2023Zhang et al, 2017). In this study, a more strenuous antioxidant system might be plausible due to the efficient uptake of inorganic ions as osmotic adjustment (Table 4), which saves energy and eventually results in increased antioxidant (SOD, POD, and CA) activity under combined drought and salt stress (Figure 5).…”
Section: Upregulation Of Antioxidant Enzymes Under Combined Drought A...mentioning
confidence: 99%
“…Extensively distributed along with the marginal lands of Pakistan, this C4 perennial grass is utilized as a typical fodder. Detailed investigations have been conducted to characterize the physiological, molecular, and biochemical markers of salt tolerance in this fodder grass (Hussain et al, 2015;Hussain et al, 2021). Our previous work distinguished single and combined effects of drought and salinity stress on the gas exchange properties of this grass (Hussain et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq and iTRAQ analysis of aphids before and after CMV (cucumber mosaic virus) infection identified 20,550 DEGs, however, only 744 DEPs were obtained [ 71 ]. In the study of salt tolerance of Panicum antidotale, 3179 DEGs were detected by RNA-seq at the salt concentration of 100 mM, while only 514 DEPs were identified by Liquid Chromatography Tandem Mass Spectrometer (LC-MS/MS) in the same environment [ 72 ]. In the conjoint analysis of the transcriptomic and proteomic data in this study, gene expression level is often not consistent with its protein accumulation level.…”
Section: Discussionmentioning
confidence: 99%